2016
DOI: 10.1007/978-3-319-40415-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram Identification: Use a Simple Set of Features in QRS Complex to Identify Individuals

Abstract: This paper presents a Multilayer Perception Neural Network developed to identify human subjects using electrocardiogram (ECG) signals. We use the amplitude values of Q, R and S as a features for our experiments. In this study, a total of 87 dataset were collected among 14 subjects from the Physikalisch-Technische Bundesanstalt (PTB) database. Out of the 14 subjects, Q-R-S feature points were taken from different day and time sessions to perform classification with MLP. Out of this data, 66 % is used as trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…HR variability can be removed under short-term ECG signal condition and avoid the complex operations of accurate Q detection or HR measurement. Based on the experiments, it is found that not only the amplitude, but also the temporal and morphological information of QRS can potentially contribute to identification, which is in accordance with other studies [5,20,21]. Second, the proposed method can achieve high heartbeat identification accuracy, which makes it suitable for systems that use a small quantity of heartbeats to make a decision [49].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…HR variability can be removed under short-term ECG signal condition and avoid the complex operations of accurate Q detection or HR measurement. Based on the experiments, it is found that not only the amplitude, but also the temporal and morphological information of QRS can potentially contribute to identification, which is in accordance with other studies [5,20,21]. Second, the proposed method can achieve high heartbeat identification accuracy, which makes it suitable for systems that use a small quantity of heartbeats to make a decision [49].…”
Section: Discussionsupporting
confidence: 83%
“…To preserve all potential identity information of the QRS complex, we use a length-fixed window to keep the QRS complex original. Secondly, it is also found that mapping the heartbeat into a regular interval of segments does help to deal with the HR variability problem [5,20]. Thus, we segment the heartbeat into three parts, which are the first, the QRS and the third part respectively, and unify them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In prior literature, Nemirko et al [5] firstly pointed out that QRS complex did not change significantly with the heart rate varying, and was able to perform as a stable characteristic. Later, Tuerxunwaili et al [31] found that using only three QRS based features was sufficient to identify a subject, which further highlighted the importance of QRS complex. Actually, to our knowledge, nearly all the existing ECG based biometric identification methods have taken QRS complex or its related form as features.…”
Section: Feature Selectionmentioning
confidence: 99%